STUDENTSâ€™ PERCEPTION ON THE USE OF JOHNY GRAMMARâ€™S WORD CHALLENGE APPLICATION IN LEARNING PREPOSITIONS - Aisyah Nur Syafani; Tahrun Tahrun; Evi Rosmiyati (Universitas PGRI Palembang, 2021)
The main problem of this study isÂ â€œWhat were the eleventh grade studentsâ€™ perception on the use Johnny grammarâ€™s word challenge application in learning prepositions and the impact of Johnny grammarâ€™s word challenge application the eleventh grade at PGRI Vocational High School 2 of Palembang?â€. This study aimed to investigate the eleventh grade studentsâ€™ perception on the use Johnny grammarâ€™s word challenge application in learning prepositions at PGRI Vocational High School 2 of Palembang. This data acquired from questionnaires based on four indicators, this research used a descriptive qualitative method in this study. Based on the achievement of the questionnaire, it can be concluded that all indicator high category shows that amounts to 9 (16.36%) students which means the students have comprehension ability is fair, the indicator medium category shows that amounts to 41(74.54%) students which means all of the students understand Johnny Grammarâ€™s Word Challenge Application and the low category shows that amounts to 11 (20%) students which means the students half of them can not able to understand Johnny Grammarâ€™s Word Challenge Application. So, it can be concluded that using Johnny Grammarâ€™s Word Challenge Application can help students learn prepositions